Teachers of Arts and Culture and the Continuing Professional Development - Sri Kristati (Imaji, 2015)
The teaching profession has consequences and  it  needs programmed and continuing guidance and development strategies to support the improvement of professionalism. Through Continuing Professional Development, teachers can maintain, improve, and develop knowledge and skills to implement learning processes professionally and optimally. Quality learning is expected to be capable of improving students’ knowledge, skills, and attitudes. Continuing Professional Development  from the aspect of professional development is expected to assure that every teacher can attain and  fulfil  the competency standard and acquire competencies in accordance with the professionalism level and can provide standard and quality services in learning in order for learners  to be capable of developing themselves  based on their potentials. From the aspect of  career development, Continuing Professional Development  can assure teachers in obtaining credit points that they need for their career levels, having opportunities to develop their professional careers based on their wishes, and developing their professional experiences based on their responsibilities.